The influence of leadership, discipline, and workload on employee performance through job satisfaction as an intervening variable in Regional Revenue Agency Riau Islands Province - Firaldi, Yukiko; Wibisono, Cablullah; Ngaliman, Ngaliman; Indrayani, Indrayani; Satriawan, Bambang (Journal of Multidisciplinary Academic Business Studies, 2023)
Purpose: This research aimed to investigate the influence of leadership, discipline, and workload on employee performance through job satisfaction in the Regional Revenue Agency of Riau Islands Province. Research Methodology: This study used a quantitative research approach, with a sample size of 128 employees selected using probability sampling with simple random technique. The data obtained were analyzed using Partial Least Square (PLS) with two evaluation stages, namely the measurement model and the structural model. Results: The results indicate that workload had no significant direct influence on job satisfaction, but had a positive and significant relationship with employee performance. On the other hand, discipline had a significant direct influence on job satisfaction, but no significant direct influence on employee performance. Leadership had a significant direct influence on both job satisfaction and employee performance. Job satisfaction did not have a significant direct influence on employee performance. Conclusions: Leadership is the key factor enhancing both job satisfaction and employee performance, while discipline affects satisfaction and workload directly influences performance. Limitations: Overall, the study findings highlight the importance of leadership in fostering job satisfaction and employee performance in the Regional Revenue Agency of Riau Islands Province. Contribution: These insights can provide valuable guidance for organizational managers to optimize the work environment and promote employee engagement and productivity.